El tratamiento fisioterapéutico ¿es efectivo en el mantenimiento físico y en la reducción del declive cognitivo de las demencias? - Christofoletti, Gustavo [UNESP]; Mércia Oliani, M. [UNESP]; Gobbi, S. [UNESP]; Stella, F. [UNESP]; Bucken Gobbi, L. T. [UNESP]; Del Rosario Sánchez Arias, M. [UNESP] (Elsevier, 2008)
Introduction. Dementia is a chronic and neurodegenerative disease responsible for a progressive decline of cognition and physical capacity. Objective: To verify the effectiviness of three months of physiotherapy intervention on cognitive functions and balance of institutionilized elderly people with dementia. Patients and methods. This study has comprised thirty subjects, divided in two groups: EG (experimental group) and CG (control group). EG was composed by 15 participants with mean age of 71,6 ± 8,5 years and scholarity of 4,7 ± 4,2 years. CG was formed by 15 subjects with mean age of 78,5 ± 7,6 years and scholarity of 2,2 ± 1,8 years. The sample was evaluated by means of the following instruments: Mini-Mental State Examination, Semantic Verbal Fluency test, Clock Drawing test, Berg Balance Scale and Timed Get Up and Go test. The statistical procedures were done by means of Multivariate Analisis of Variance (MANOVA), with significance of 5 % (p < 0,05). Results. The results has shown a heterogeneity of both groups related to age (F = 0,2, p < 0,05) and scholarity (F = 2,6, p < 0,05). MANOVA pointed beneficts of physiotherapy on balance (F = 7,3, p < 0,01) but not on cognitive functions (F = 0,3, p > 0,05). Conclusions. Three months of physiotherapy were effective to improuve physical capacity of institucionilized elderly people with dementia. Neverthless, it was not able to minimize cognitive decline commonly seen on dementia. The question if a prolonged intervention could propitiate cognitive beneficts remains, specially in a more homogeneous groups.
Is physical therapy effective in physical maintenance and in the reduction of the cognitive decline in dementias?
Keywords: Balance; Cognitive functions; Dementia; Elderly people; Instututionalized; Physiotherapy